Impact of orange essential oil on enteric methane emissions of heifers fed bermudagrass hay - Jiménez-Ocampo, Rafael; Montoya-Flores, María D.; Pamanes-Carrasco, Gerardo; Herrera-Torres, Esperanza; Arango, Jacobo; Estarrón-Espinosa, Mirna; Aguilar-Pérez, Carlos F.; Araiza-Rosales, Elia E.; Guerrero-Cervantes, Maribel; Ku-Vera, Juan C. (Frontiers in Veterinary Science, 2022)
In this study, the effects of orange essential oil (OEO) on the rumen fermentation, nutrient utilization, and methane (CH4) emissions of beef heifers fed a diet of bermudagrass (Cynodon dactylon) were examined. In addition, in vitro and in situ experiments were conducted. The in vitro experiment consisted of three treatments: control (CTL, no OEO), OEO1 (0.25% OEO), and OEO2 (0.5% OEO). The forage to concentrate ratio was 70:30 (dry matter [DM] basis) in all treatments. No changes in pH, proportions of volatile fatty acids, and the acetate:propionate ratio were observed (P > 0.05). The addition of 0.25% OEO resulted in a reduction in CH4 production (mL/g) relative to the control (P < 0.05). In the in situ experiment, 5 g of total mixed ration (CTL, OEO1, and OEO2) were incubated for 6, 12, 24, 48, and 72 h. Potential and effective degradability were not affected by OEO supplementation (P > 0.05). In the in vivo study, six crossbred beef heifers (Bos indicus × Bos taurus), fitted with rumen cannulas, were assigned to three different treatments: no additive (CTL), 0.25% OEO (OEO1), and 0.5% OEO (OEO2) in a replicated 3 × 3 Latin square (21-day periods). Heifers were fed at 2.8% body weight. In vivo CH4 production was measured in open-circuit respiration chambers. Reductions in gross energy consumption, apparent total tract digestibility, and rumen valerate concentration were observed for OEO2 compared to the control (P < 0.05). Additionally, decreases in CH4 emissions (g/day; P < 0.05) and CH4 (MJ gross energy intake/day; P < 0.05) were observed in response to supplementation of 0.5% OEO as compared to the CTL treatment. Thus, supplementation of 0.5% OEO reduced CH4 emissions (g/day) by 12% without impacting the DM intake of heifers fed bermudagrass hay as a basal ration.